Molecular identification of the wheat male fertility gene Ms1 and its prospects for hybrid breeding - Elise J. Tucker (Nature Portfolio, 2017)
Heterosis can rapidly boost yield in crop species but development of hybrid-breeding systems for bread wheat remains a challenge. Here, Tucker et al. describe the molecular identification of the wheat Ms1 gene and discuss its potential for large-scale hybrid seed production in wheat.